Determinants of Students Academic Satisfaction of Semarang State University Postgraduate Program - Rusdarti, Rusdarti (Educational Management, 2019)
Academic service is a service directly related to students, in which college shall, in this case UNNES Postgraduate Program, in providing services attempt to understand and meet students needs, and eventually leads to students perception. A quality academic service will satisfy students. This research aims at (1) describing and analyzing academic satisfaction and service quality (2) analyzing the contribution of service quality to students academic satisfaction (3) determining most dominant contribution to students academic satisfaction at Postgraduate Program, UNNES.This quantitative descriptive research employs multiple regression and correlation analyses. Primary data in relation to academic satisfaction and service quality variables as well as all of their dimensions are used in this research.The research results show that: (1) the academic satisfaction and service quality perceived and received by students of Postgraduate Semarang State University are good. Descriptively, the result of academic satisfaction of communication dimension is the highest, while tangible is the highest dimension of service quality; (2) the contribution of service quality to students academic satisfaction is 50.5%. The result is marked positive, which means that better service quality will improve students academic satisfaction of UNNES Postgraduate Program; and (3) the contribution of service quality of tangible dimension to students academic satisfaction is most dominant at UNNES Postgraduate program.Educational staffs, lecturers and chairman of UNNES Postgraduate Program are suggested to improve services in responsiveness dimension and how to respond to students in providing them services, since it is the lowest dimension with lower than point three or below the average. The service quality of tangible dimension should be continuously maintained since it makes the most dominant contribution to determining students academic satisfaction.